2005
DOI: 10.1002/adma.200501549
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Templated Silver Nanorings

Abstract: Nanostructures of noble metals with well-defined shapes and sizes are increasingly attracting the attention of scientists in the fields of catalysis, electronics, photonics, information storage, optoelectronics, biological labeling, etc. The further development and practical applications of nanostructures are expected to increase rapidly because of their interesting optical, electronic, and magnetic properties. [1] In this context, important knowledge of the direct preparation of metallic nanostructures of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
106
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 30 publications
(31 reference statements)
2
106
0
1
Order By: Relevance
“…[ 1 , 2 ] It has been shown that DNA can be precisely designed with specifi c sequences and self-assemble into two-or three-dimensional nanostructures, [3][4][5][6][7][8][9] fabricated to nanomachines or motors, [10][11][12][13] or used as a programmable template to direct the assembly of nanoparticles. [14][15][16][17] Recently, the concept of DNA assembly has been expanded to construct "DNA hydrogels", which are crosslinked networks swollen in an aqueous phase. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Though hydrogels have great potential in biological and medical applications, [32][33][34][35][36] such as drug and gene delivery, biosensing, and tissue engineering, studying the preparation of DNA hydrogels with designable properties is still in its early stages.…”
Section: Doi: 101002/adma201003343mentioning
confidence: 99%
“…[ 1 , 2 ] It has been shown that DNA can be precisely designed with specifi c sequences and self-assemble into two-or three-dimensional nanostructures, [3][4][5][6][7][8][9] fabricated to nanomachines or motors, [10][11][12][13] or used as a programmable template to direct the assembly of nanoparticles. [14][15][16][17] Recently, the concept of DNA assembly has been expanded to construct "DNA hydrogels", which are crosslinked networks swollen in an aqueous phase. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Though hydrogels have great potential in biological and medical applications, [32][33][34][35][36] such as drug and gene delivery, biosensing, and tissue engineering, studying the preparation of DNA hydrogels with designable properties is still in its early stages.…”
Section: Doi: 101002/adma201003343mentioning
confidence: 99%
“…27,28 Here, to the best of our knowledge, we report for the first time a novel and simple strategy for the synthesis of Au nanorings via a one-pot direct solution-based chemical reaction by means of an unusual stress-driven structure collapse and etching mechanism. The as-formed Au nanorings with tailored structures are an exciting new member of the family of Au nanostructures with diverse shapes.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Compared to silver nanowires, silver nanorings have less plasmon-propagation loss and higher sensitivity as biosensors in the near-infrared region. [42] Several methods (such as nanostructured template and lithography techniques) have been proposed to prepare silver and gold nanorings; [43][44][45][46][47][48] however, the nanorings prepared thus are polycrystalline. The growth of silver nanorings in the form of a singly twinned crystal is a hard challenge and has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%